2008
DOI: 10.1289/ehp.11338
|View full text |Cite
|
Sign up to set email alerts
|

Global DNA Hypomethylation Is Associated with High Serum-Persistent Organic Pollutants in Greenlandic Inuit

Abstract: BackgroundPersistent organic pollutants (POPs) may influence epigenetic mechanisms; therefore, they could affect chromosomal stability and gene expression. DNA methylation, an epigenetic mechanism, has been associated with cancer initiation and progression. Greenlandic Inuit have some of the highest reported POP levels worldwide.ObjectiveOur aim in this study was to evaluate the relationship between plasma POPs concentrations and global DNA methylation (percent 5-methylcytosine) in DNA extracted from blood sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

27
230
2
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 323 publications
(261 citation statements)
references
References 44 publications
27
230
2
2
Order By: Relevance
“…However, we used the most technologically advanced and validated methods currently available for LINE-1 methylation analysis and have already demonstrated a relationship between higher LINE-1 and male sex and several other obesity-related risk factors in offspring in early life. 17 This method for LINE-1 methylation analysis has been shown in previous investigations to be sensitive to environmental and host-related factors, including age, 18 sex, 16,19 smoking 20 and tobacco smoke components, 21 physical activity 22 and environmental pollution. [23][24][25][26] Also, we measured DNA methylation only in blood DNA and we cannot exclude that methylation changes due to dietary components might be present in other tissues in the same individuals.…”
Section: Resultsmentioning
confidence: 99%
“…However, we used the most technologically advanced and validated methods currently available for LINE-1 methylation analysis and have already demonstrated a relationship between higher LINE-1 and male sex and several other obesity-related risk factors in offspring in early life. 17 This method for LINE-1 methylation analysis has been shown in previous investigations to be sensitive to environmental and host-related factors, including age, 18 sex, 16,19 smoking 20 and tobacco smoke components, 21 physical activity 22 and environmental pollution. [23][24][25][26] Also, we measured DNA methylation only in blood DNA and we cannot exclude that methylation changes due to dietary components might be present in other tissues in the same individuals.…”
Section: Resultsmentioning
confidence: 99%
“…LINE-1, Alu and AluYb8 methylation did not differ between current and never/former smokers. 17,21,37,41,57,69 Some studies recruited small number of subjects; however, the overall consistency of the results suggests that genomic DNA methylation levels are not affected by active smoking exposure in adulthood.…”
mentioning
confidence: 95%
“…41,57 In 70 Greenlandic Inuit, a population presenting some of the highest reported levels of POP worldwide, a significant inverse linear relationship was found for DDT, DDE, β-hexachlorocyclohexane, oxychlordane, α-chlordane, mirex, several PCBs and the sum of all persistent organic pollutants with Alu methylation. 57 However, as the exposure levels in Greenlandic Inuit are much higher than those in the US general population, it is unclear whether the findings apply to other populations with lower exposures. A study in Korea 41 found that most organochlorine (OC) pesticides were inversely and significantly associated with Alu methylation.…”
mentioning
confidence: 98%
“…The serum concentrations of HCB, -HCH, p,p'-DDE, oxychlordane, and trans-nonachlor increased with increasing age and were significantly higher in the 60 years and older age group (CDC, 2005;Patterson et al, 2009). Because the general population was exposed to these pesticides by eating contaminated fatty food such as fish, an Inuit population in Greenland showed high levels of exposure (Rusiecki et al, 2008). Serum samples were collected from 70 Greenlandic Inuit (61 men, 9 women) under the Arctic Monitoring and Assessment Program (AMAP) in 1997-1998.…”
Section: Levels Of Organochlorine Pesticides In the North American Pomentioning
confidence: 99%